2011
DOI: 10.1017/s1041610211000342
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Italian version of the AADS questionnaire: a caregiver-rated tool for the assessment of behavioral deficits and excesses in persons with intellectual disabilities and dementia

Abstract: These results confirm the reliability and validity of the Italian version of AADS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…2022); since the AILMS is focused on assessing advanced instrumental activities and high order executive functioning, then it may be more sensitive to detecting early changes compared with other informant‐rated scales that assess changes in more simple or basic daily abilities, such as the DMR‐I (De Vreese et al . 2007) and DSQIID‐I (Gomiero et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2022); since the AILMS is focused on assessing advanced instrumental activities and high order executive functioning, then it may be more sensitive to detecting early changes compared with other informant‐rated scales that assess changes in more simple or basic daily abilities, such as the DMR‐I (De Vreese et al . 2007) and DSQIID‐I (Gomiero et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in daily abilities, in the absence of new-onset organic or mental health problems associated with an incipient cognitive decline, may predict dementia (Deb et al 2022); since the AILMS is focused on assessing advanced instrumental activities and high order executive functioning, then it may be more sensitive to detecting early changes compared with other informant-rated scales that assess changes in more simple or basic daily abilities, such as the DMR-I (De Vreese et al 2007) and DSQIID-I (Gomiero et al 2017). Future longitudinal studies are required to determine the usefulness of the AILMS to assess dementia-related functional decline in adults or seniors with IDD.…”
Section: Future Use and Other Applications Of The Ailmsmentioning
confidence: 99%
“…The discriminant validity of AFAST‐I was checked by the use of the sub‐scale of an Italian version of the Assessment for Adults with Developmental Disabilities (De Vreese et al . ). This informant‐based scale quantifies the frequency of 11 behavioural excesses which have occurred in the last two weeks (e.g.…”
Section: Methodsmentioning
confidence: 97%
“…Cross-Sectional Studies Including Participants with DS and other IDThe DLD[38,39,40] revealed good psychometric properties in studies with participants with both DS as other ID. Eight studies used the DLD[47,61,62,63,64,65,66,67] Shultz et al (2004).…”
mentioning
confidence: 99%